An LCA of French beans from Kenya for decision-makers - Claudine Basset-Mens; Andrew Edewa; Céline Gentil (Indonesian Life Cycle Assessment Network (ILCAN), 2019)
Although challenging, private and public decision-makers increasingly demand for quantitative assessments of the environmental performance of value chains in South contexts. This paper presents and critically analyzes a complete LCA study performed with Endpoint indicators for a public decision-maker for the fresh French bean (FB) value chain of Kenya. A cradle-to-market-gate LCA study was done including five main stages: agricultural production, transport by road before pack-house, pack-house, transport by road after pack-house, intercontinental transport by air-freight and using 1 kg of raw French bean processed as functional unit. Supported by local experts, primary data were collected for all inputs and outputs for 33 farms over 5 counties and 2 pack-houses. An expert-based typology defined four farm types: large-farm, medium-farm, small-holder farm (SHF) contracted and small-holder farm scattered. Best available methods for field emissions were used and adapted when possible to local conditions (e.g. P losses). At market-gate, air-freight was identified as main hot-spot pleading for the design of stabilized FB products that could be sea-freighted. At farm-gate, large differences were observed between farm types and fertilizer, water and land use were the key-drivers of their eco-efficiency. Impacts due to pesticides applications were small at Endpoint level but were incomplete. These results should be validated with a greater sample of stakeholders and the scope of the LCA should be extended to the consumption stage. Research is also needed to provide LCA practitionners with operational and reliable tools for a better inclusion of pesticides’ impacts and uncertainty.